Regional and Facility Differences in Interventions for Mastitis by Australian Physiotherapists. - Diepeveen, L.; Fraser, E.; Croft, A.; Jacques, A.; McArdle, A.; Briffa, K.; McKenna, Leanda (Sage Science Press, 2018)
BACKGROUND:: Little information has been documented regarding interventions for mastitis by Australian physiotherapists. It is currently not known if physiotherapy interventions vary across Australian regions and types of healthcare facilities. RESEARCH AIMS:: (1) To identify the interventions used by Australian physiotherapists treating mothers with mastitis and (2) to determine the variability in interventions used across regions and facilities. METHODS:: A retrospective observational design was used. A sample of case records of mothers with mastitis was identified (N=192). These case records documented physiotherapy interventions for mastitis in hospitals and private physiotherapy practices in Western Australia ( n=77; 40.1%), Victoria ( n=76; 39.6%), and New South Wales ( n=39; 20.3%). An electronic data collection tool was designed to examine intervention variables. RESULTS:: The physiotherapy interventions received by mothers included therapeutic ultrasound (n=175; 91.1%), education and advice (n=160; 83.3%), and massage (n=103; 53.6%). Therapeutic ultrasound parameters varied across regions and types of healthcare facilities. Mean documented therapeutic ultrasound intensity was approximately twice as high in New South Wales and Victoria than in Western Australia. CONCLUSIONS:: Regional and facility differences exist in physiotherapy interventions for mastitis in Australia. Healthcare professionals who refer to physiotherapists for mastitis should be aware that interventions received may differ across regions and facility types.